Терминот ὕλη во контекст на Аристотеловата филозофија ‒ преводни предизвици, дилеми, решенија - Џукеска, Елена (Филозофско друштво на Македонија, 2017)
The Greek word ὕλη which means "forest, trees, brushwood, undergrowth, twigs, timber, firewood, material", but also "shrub, ivy", in the sense of a "plant that can interweave, creep and grow as a hedge", in Aristotle's works receives for the first time an abstract meaning that corresponds to the meaning of the Latin term "matter". The interpretation and translation of the term ὕλη in Aristotle's works is an endless challenge for the researchers and translators. The contribution that follows, contains translations, accompanied with brief philological commentaries of ten passages from "History of Animals", "Physics" and "Metaphysics", in which the term ὕλη is found, that have not been yet translated into Macedonian language and were subject of discussion at the workshop entitled "The term ὕλη in the context of Aristotle's Philosophy ‒ challenges of translation, dilemmas, solutions", held on 16-th of March 2016 at the Faculty of Philosophy. The translations of these passages explore more specifically the question to what extent does the Slavic word "plot", meaning "fence, but also plant that grows as a shrub and can be interwoven and shaped", properly reflects the polysemy of Aristotle's term ὕλη, but at the same time they aim to answer other questions as well, significant for the translation of Aristotle's works and for translation in general.
The term ὕλη in the context of Aristotle's Philosophy ‒ Translation Challenges, Dilemmas, Solutions